Avaliação nutricional do feno das folhas da amoreira (Morus alba L.) em frangos de corte - Dorigan, Claudia Josefina; Resende, Kleber Tomaz De [UNESP]; Alessi, Antonio Carlos [UNESP]; Malheiros, Euclides Braga [UNESP]; Sakomura, Nilva Kazue [UNESP] (Editora da Universidade Estadual de Maringá (EDUEM), 2011)
The trial was carried to evaluate the nutritional effects of mulberry leaf hay in broiler chickens. Five treatments were used: control (no mulberry, 3.16% CF); 15% mulberry (4.14% CF); 30% mulberry (5.09% CF), no mulberry (4.14% CF); no mulberry (5.09% CF). A randomized blocks design was used, with two blocks and three replications into the blocks to evaluate performance index, histopathological examination of the visceral organs and morphometric measurements of the hepatocyte nucleus and pancreatic acini. A poor performance index was observed for broilers feeding on mulberry leaves; lesions such as steatosis, proliferation of hepatic duct cells and multiple necrosis were found in the livers of the chickens fed with 30% mulberry (5.09% CF), as well as size reduction of the hepatocyte nucleus and pancreatic acini. From these data, it is concluded that mulberry probably has some toxic substance which can interfere in the improvement of diet ingredients, resulting in damage to broiler chickens.

O experimento foi conduzido com o objetivo de avaliar nutricionalmente o feno das folhas de amoreira, utilizando-se de frangos de corte. Foram utilizados cinco tratamentos (Testemunha (sem amoreira, 3,16% FB), 15% de amoreira (4,14% FB), 30% de amoreira (5,09% FB), Sem amoreira (4,14% FB) e Sem amoreira (5,09% FB)) usando-se o delineamento em blocos casualizados, com dois blocos e três repetições dentro de cada bloco e avaliados os índices de desempenho, o exame histopatológico dos órgãos viscerais e medidas morfométricas do núcleo dos hepatócitos e ácinos pancreáticos. Foi verificado o pior desempenho produtivo para as aves que ingeriram feno de folhas de amoreira, além de lesões tais como esteatose, proliferação de células de ductos hepáticos e necrose focal múltipla no fígado das aves alimentadas com o tratamento 30% de amoreira (5,09% FB), além da diminuição nas dimensões do núcleo dos hepatócitos e dos ácinos pancreáticos.
Nutritional assessment of mulberry (Morus alba L.) leaf hay in broilers
Keywords: Performance; Broiler chicken; histopatological analysis; Desempenho; Frangos de corte; análise histopatológica